Antibacterial Mouthwash Formulation Ethanol Extract of Kirinyuh Leaves (Chromolaena odorata (L.) R.M.King & H.Rob.) on Streptococcus mutans STCC 31987 - Erdiyati, Esti; Prabandari, Rani; Sunarti, Sunarti; Nawangsari, Desi (Jurnal Farmasi & Sains Indonesia, 2024)
Kirinyuh leaves (Chromolaeina odorata (L.) R.M.King &; H.Rob.) contain secondary metabolites in the form of flavonoids, saponins, steiroids, tannins that can inhibit the growth of antibacterial growth. Based or its antibacterial properties, kirinyuh leaf extract can be developed into mouthwash to prevent dental plaque. The purpose of this study was to determine the physical stability test of the kirinyuh leaf ethanol extract mouthwash preparation and to determine the antibacterial activity of the kirinyuh leaf ethanol extract against Streptococcus mutans ATCC 31987 bacteria, so that a formulation of the kirinyuh leaf ethanol extract mouthwash preparation could be made. Mouthwash is an antiseptic preparation that is used to clean the oral cavity and is used by gargling. The extraction used was remaceration method with 70% ethanol solvent, made in various extracts with concentrations of 10%, 20%, 30%. Further evaluation of the preparation includes : organoleptic test, pH test, viscosity test. The results of the One Way ANOVA analysis showed that there was no significant difference in the pH test, viscosity test with a p>0,05 value. Organoleptic test during 6 cycles of storage in a stable state during storage. The results showed that the ethanol extract of kirinyuh leaf mouthwash was able to inhibit the growth of Streptococcus mutans bacteria, namely in F1 the weak category was 2.43±0.81 mm, F2 was 10.21±3.56 mm the strong categori, F3 was 13.38±2.72 mm strong category. Keywords : Antibacterial, Kirinyuh leaves, Mouthwash